Imaging and spectroscopy techniques applied to characterise fossilisation processes and biomineralisation - Oses, Gabriel Ladeira; Belatto, Sabrina Larissa; Limeira Junior, Silvio Cesar Marqui; dos Santos, Túlio Paulino; Rodrigues, Cleber Lima; Prado, Gustavo Marcondes Evangelista Martins; Dias, Jaime; Carvalho, Ismar De Souza; da Silva, Tiago Fiorini; Rizzutto, Marcia de Almeida (Frontiers in Ecology and Evolution, 2025)
Palaeontology has long benefited from advancements in technology, allowing more refined morphological and compositional characterisation of fossils, relying on non-destructive and non-invasive techniques. Besides the improvement of existing technology and the development of new instruments, techniques, and data processing methods, the combination of imaging and of spectroscopy techniques lay at the core of palaeometry, as it has proven to be a powerful approach to disentangle morphological and geochemical diagenetic imprints, which potentially bias the identification of primary signals in fossils, those of which have palaeobiological significance. This rationale is applicable to the investigation of soft-tissue mineralisation and to the study of the earliest biomineralising animals, in which diagenesis affects primary composition and morphology. Here, we show the application of ionoluminescence (IL) by means of proton beams in an accelerator to yield images of unprepared calcareous fossils (earliest skeletal animals from the Ediacaran Tamengo Formation, Brazil) and of fossils preserved in carbonate rocks (fossil insects from the Cretaceous Crato Formation, Brazil), discussing the benefits of this method over conventional cathodoluminescence (CL). We also provide a UV-light-based imaging (ultraviolet fluorescence photography, UVF) study of the same array of fossils, which enabled the distinction of different mineralogical compositions at fossil insects. This imaging technique has guided the application of X-ray fluorescence (XRF) and micro-Raman spectroscopy (micro-RS) techniques, confirming heterogeneous mineralogical compositions over the fossils. Finally, radiography of these fossil insects (and arachnids) reveals the potential of this technique to the characterisation of internal soft tissues and of morphological features hidden in the calcareous host rock of the Crato Fm. fossils, thus improving taxonomic identification in a non-destructive way.